2019
DOI: 10.1007/s13202-019-0708-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a multi-branch gas–liquid pipe separator using computational fluid dynamics

Abstract: The present paper aims to evaluate the performance of a multi-branch gas-liquid pipe separator by means of 3D computational fluid dynamics. This type of separator is attractive for deepwater subsea hydrocarbon fields due to its compactness and reduced weight when compared against traditional gravity vessel separators. The focus of this paper is on studying the internal flow dynamics, the separation efficiency, and the performance with changing and transient operating conditions. Numerical simulations were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…The liquid holdup that existed during the critical ZNLF is called critical ZNLF holdup. By grouping some of the critical ZNLF holdup, a trend was realised that agreed with existing data by Kouba et al, and Apardi et al, that is: the critical ZNLF holdup decrease with increasing separator inlet superficial gas velocity [4,6]. Additionally, it was found that the critical ZNLF holdup increases with increasing separator inlet superficial liquid velocity.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The liquid holdup that existed during the critical ZNLF is called critical ZNLF holdup. By grouping some of the critical ZNLF holdup, a trend was realised that agreed with existing data by Kouba et al, and Apardi et al, that is: the critical ZNLF holdup decrease with increasing separator inlet superficial gas velocity [4,6]. Additionally, it was found that the critical ZNLF holdup increases with increasing separator inlet superficial liquid velocity.…”
Section: Resultssupporting
confidence: 81%
“…Liquid holdup under ZNLF for a stagnant liquid condition was measured using electrical resistance tomography. The trend of present data of ZNLF holdup under stagnant liquid condition agrees with that reported by Kouba et al, [4] and Apardi et al, [6]. However, quantitatively, their data are not comparable with the present data, as the effect of inlet liquid flow on ZNLF was not considered in their work.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The curve increases gently at first, then rises rapidly, then increases slowly and then reaches a peak and begins to decline in a symmetrical form. This model is more suitable for predicting the growth law of natural gas reserves with relatively gentle changes (Mfoubat and Zaky 2019;H Refsnes., Diaz M., Stanko M. 2019).…”
Section: Gauss Model Of Natural Gas Reserves Predictionmentioning
confidence: 99%